Developing the Speech of Children with Hearing Impairments Based on Digital Technologies - Naimova , Muxlisa (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article discusses the pedagogical and methodological foundations of using digital technologies in the process of speech development of children with hearing impairments. During the research, the impact of interactive learning tools, multimedia technologies, electronic learning platforms, and information and communication technologies on speech development was analyzed. The results of the study showed that lessons organized on the basis of digital technologies play an important role in improving children’s pronunciation skills, expanding their vocabulary, and activating their communicative activity.